HUMANITARIZATION OF HIGHER TECHNICAL EDUCATION: PSYCHOLOGICAL AND PEDAGOGICAL ASPECT - А.А. Slobodyanyuk; V.M. Лyс (Academy of Cognitive and Natural Sciences, 2022)
The article deals with the organization of studying psychological and pedagogical subjects for students of technical universities.